Pengaruh Konsep 'New Woman' dalam Karya Kate Chopin dalam Perkembangan Sastra Amerika - Raudhatul Jannah, Msy. Siti (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
This article explores Kate Chopin's contribution to shaping the concept of the New Woman, which significantly influenced the development of American literature in the late 19th and early 20th centuries. Against the backdrop of the post-Civil War era in the United States, marked by social changes and the growing women’s emancipation movement, this study examines how Chopin, through her seminal works The Awakening and The Story of an Hour, presents a discourse on women’s individual freedom and resistance to traditional gender norms. The analysis employs the framework of the New Woman, introduced by Sarah Grand, to highlight Chopin’s ideas about women’s autonomy over their lives and emotions. The article concludes that Chopin’s works played a pivotal role in creating narratives that reject gender constraints, assert personal identity, and demand emotional independence, all of which became foundational to feminist literature. Thus, Chopin is recognized not only as a pioneer of the New Woman in American literature but also as a visionary who continues to influence how literature portrays women’s freedom and experiences.